On correlation functions of higher-spin currents in arbitrary dimensions d > 3 - Melik Karapetyan; Ruben Manvelyan; Karapet Mkrtchyan (Journal of High Energy Physics, 2024)
Abstract We revisit the problem of classification and explicit construction of the conformal three-point correlation functions of currents of arbitrary integer spin in arbitrary dimensions. For the conserved currents, we set up the equations for the conservation conditions and solve them completely for some values of spins, confirming the earlier counting of the number of independent structures matching them with the higher-spin cubic vertices in one higher dimension. The general solution for the correlators of conserved currents we delegate to a follow-up work.